Multinational enterprises: Comparing performance-related pay between companies in Eastern and Western Europe. (April 2015) - Poutsma, Erik; Moerel, Hans; Ligthart, Paul EM
This article compares the spread of broad-based individual performance-related pay practices (PRP) in Central and Eastern European (CEE) and Western European companies. The article investigates the dominance effect of multinational enterprises (MNEs) and the constraining effects of industrial relations, i.e. collective bargaining and union influence. A key finding is that we did not find stronger influence by US MNEs compared with other MNEs. Regarding the determinants of industrial relations, in general decentralised firm-level bargaining supports the adoption of PRP schemes, whereas a greater degree of unionisation tends to reduce it. However, the latter effect is not found in CEE countries with their more permissive industrial relations system. The fact that there are high levels of broad-based individual PRP in CEE, that there is no negative association with unionisation and a positive relationship with firm-level bargaining and no effect of MNEs suggests that this practice is well established in firms in CEE.